PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ONLINE TERHADAP PRESTASI BELAJAR SISWA MELALUI MINAT BELAJAR - Diana Yani Fallo; Maria Sogen; Elen Roga (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2022)
This type of research was quantitative with an experimental method. The procedure employed in this research was the class was given a pre-test and post-test as well as the results of the validity test, reliability test, normality test, and hypothesis test. Reliability was used to measure an instrument with two or more answer choices and for an instrument with more than two answer choices. It is said to be reliable if the Cronbach Alpha reliability coefficient is between 0.70 - 0.90 and the results obtained from the results of the questionnaire validity test are 0.721. The test results showed that the use of learning media influences students' achievement.